Santri dan Nasionalisme - Gufron, Iffan Ahmad (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2019)
This Paper clarifies the close connection between santri and nationalism. Asking the nationalism of santri it means forgetting the history of NKRI (Unitarian State of Indonesia). The history book of indonesia from colonial era or pre-independence era, independence era to post-independence era told the big contribution of santri in all era. Pesantren as the genuine institution of islamic education in indonesia which creates santri was built for educating indonesian resources. So, nationalism for santri as graduate of pesantren is contributes in various filelds of life in Indonesia.Keywords: Santri, Nasionalism, Indonesia